Novel Raman Parametric Hybrid L-Band Amplifier with Four-Wave Mixing Suppressed Pump for Terabits Dense Wavelength Division Multiplexed Systems. (15th February 2016) - Kaur, Gaganpreet; Sharma, Sanjay; Kaur, Gurmeet
Abstract : We demonstrate improved performance of parametric amplifier cascaded with Raman amplifier for gain of 54.79 dB. We report amplification of L-band using 100 × 10 Gbps Dense Wavelength Division Multiplexed (DWDM) system with 25 GHz channel spacing. The gain achieved is the highest reported so far with gain flatness of 3.38 dB without using any gain flattening technique. Hybrid modulated parametric pump is used for suppressing four-wave mixing (FWM) around pump region, resulting in improvement of gain flatness by 2.42 dB. The peak to peak variation of gain is achieved less than 1.6 dB. DWDM system with 16-channel, 25 GHz spaced system has been analyzed thoroughly with hybrid modulated parametric pump amplified Raman-FOPA amplifier for gain flatness and improved performance in terms of BER andQ -factor.